2016
DOI: 10.1002/ams2.222
|View full text |Cite
|
Sign up to set email alerts
|

Severe sepsis caused by Capnocytophaga canimorsus complicated by thrombotic microangiopathy in an immunocompetent patient

Abstract: CaseA 61‐year‐old man with an unremarkable medical history was admitted with fever 7 days after being bitten by his dog. On day 3, he showed altered mental status, and laboratory data showed progressive hemolytic anemia, thrombocytopenia, hyperbilirubinemia, renal dysfunction, coagulopathy, and schistocytosis. Severe sepsis complicated with thrombotic microangiopathy caused by Capnocytophaga canimorsus was suspected.OutcomePlasma exchange was applied to treat the thrombotic microangiopathy and resulted in plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…We searched the PubMed, for English-language reports of cases of C. canimorsus infection complicated by TMA and identified 10 cases, summarized in Table (1,6-13). The ADAMTS13 activity was measured in only two previous case reports (6,7) and was normal, as in the present case. This phenomenon has been described in some pathogenic organisms, such as bacteria, angioinvasive fungi, viruses, and rickettsiae, that cause endothelial injury (14).…”
Section: Discussionmentioning
confidence: 99%
“…We searched the PubMed, for English-language reports of cases of C. canimorsus infection complicated by TMA and identified 10 cases, summarized in Table (1,6-13). The ADAMTS13 activity was measured in only two previous case reports (6,7) and was normal, as in the present case. This phenomenon has been described in some pathogenic organisms, such as bacteria, angioinvasive fungi, viruses, and rickettsiae, that cause endothelial injury (14).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, systemic bleeding and DIC could be the causes of death in our patient. Some previous reports have indicated that C. canimorsus sepsis causes secondary thrombotic microangiopathy, which improves with antimicrobial agents, plasma transfusion, and plasma exchange 12–14 . However, these reports did not include a progressively fatal case similar to ours.…”
Section: Discussionmentioning
confidence: 52%
“…Some previous reports have indicated that C. canimorsus sepsis causes secondary thrombotic microangiopathy, which improves with antimicrobial agents, plasma transfusion, and plasma exchange. [12][13][14] However, these reports did not include a progressively fatal case similar to ours. In our case, few findings suggested hemolysis, and fibrinogen levels decreased, which is not typical for thrombotic microangiopathy.…”
Section: Discussionmentioning
confidence: 62%
“…However, C. canimorsus causes sepsis, especially in patients with prior splenectomy, or meningitis [13]. A recent report described severe sepsis with thrombotic microangiopathy caused by C. canimorsus in an immunocompetent patient [14]. Capnocytophaga species are extremely rare as the causative organism of PD-related peritonitis.…”
Section: Discussionmentioning
confidence: 99%